Agarbathi - Prospects and Perspectives - Katwal, R. P. S.; Soni, P. L. (Indian Forester, 2002)
Industrial development in India has occurred mostly to meet increasing urban consumer needs and to support the vital agriculture sector. The traditional home based enterprises have also been simultaneously experiencing steady growth. Cottage industries have slowly changed to rural cottage or semi-urban micro-enterprises with limited assistance from government. Agarbathi making is one such industry. It has responded well to increased demand for its products both in rural and urban areas, mainly because of the continued availability of cheap labour force dominated by women and children. Agarbathi industry uses forest based raw materials like bamboo, wood, roots, barks, jigat, leaves, flowers, seeds, gums, resins and secondary derived materials like charcoal, aromatic chemicals etc. Demand for Agarbathi stick is continuously increasing both in domestic and export sector. According to one estimate international incense stick market is valued at US $ 1 billion per annum. Therefore, the demand of the raw material is likely to increase manifold in near future and lot of pressure will be on depleting forest resources. New strategy ought to be evolved to meet the challenge.